Treatment method and application of lithium-rich layered positive electrode material
By mixing the lithium-rich layered positive electrode material with the silicate solution and spray-drying and heat treatment, a modified lithium-rich positive electrode material is obtained, which solves the problem of serious structural changes in the existing materials during charging and discharging, significantly improves the structural and interface stability of the material, and improves the cycle stability and electrochemical properties.
Patent Information
- Application Number
- CN202510052554.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing lithium-rich layered positive electrode materials have severe structural changes during charging and discharging, resulting in capacity and voltage decay and poor cycle stability.
A modified lithium-rich cathode material is prepared by mixing the lithium-rich layered cathode material with a silicate solution, forming a suspension, and then spray-drying and heat-treating. This method connects particles and electrolyte through silicates to improve material structure and interface stability.
The structural stability and cyclic stability of the modified lithium-rich cathode material are significantly improved, the capacity and voltage attenuation are reduced, and physical and electrochemical properties are improved.
Smart Images

Figure CN119852365A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and more specifically, to a method for processing lithium-rich layered positive electrode materials, modified lithium-rich positive electrode materials, and lithium-ion batteries. Background Art
[0002] Nowadays, the increasing prominence of traditional energy and environmental issues has made people's demand for new energy sources more intense. Lithium-ion batteries are widely used as ideal power sources for electric vehicles and energy storage devices due to their long life and high energy conversion and storage efficiency. However, the performance of lithium-ion batteries on the market has reached a certain bottleneck. With the continuous development of science and technology and the improvement of human living standards, their energy density can no longer meet human needs. In lithium-ion batteries, positive electrode materials occupy an important part of lithium-ion batteries, which is of great significance to the energy density of batteries. Therefore, the development and improvement of positive electrode materials are of great significance.
[0003] Lithium-rich layered cathode materials are considered to be strong contenders for the "next generation cathode materials" due to their advantages in capacity and voltage window, but the improvement of their capacity depends on the redox of bulk lattice oxygen, which causes serious structural changes and gas release during the charge and discharge process of lithium-rich materials; coupled with the irreversible side reactions at the interface of electrode materials under high voltage conditions, the capacity and voltage of the materials will seriously decay during the cycle process, so it is particularly important to control the stability of the structure and interface of lithium-rich materials. Existing lithium-rich cathode materials have obvious defects and need to be improved. Summary of the invention
[0004] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for treating a lithium-rich layered positive electrode material and its application, which is used to obtain a modified lithium-rich positive electrode material, thereby enhancing the structural stability of the material, thereby improving the cycle stability and improving the physical and electrochemical properties. At the same time, the method for treating the lithium-rich layered positive electrode material has a simple process flow and is suitable for application in large-scale industrial production.
[0005] To this end, in a first aspect, an embodiment of the present invention provides a method for processing a lithium-rich layered positive electrode material, the processing method comprising the following steps:
[0006] S10, mixing silicate with deionized water in a certain ratio to prepare a silicate solution;
[0007] S20, adding the lithium-rich layered positive electrode material to the silicate solution in a certain proportion, stirring and dispersing to form a suspension;
[0008] S30, spray drying the suspension to obtain a composite powder;
[0009] S40, heat-treating the composite powder to obtain a modified lithium-rich positive electrode material.
[0010] Preferably, the silicate comprises at least one of lithium silicate, sodium silicate and lithium sodium silicate; and / or,
[0011] The concentration of the silicate solution is 0.5 g / L-5 g / L; and / or,
[0012] The mass ratio of the silicate to the lithium-rich layered positive electrode material is 1%-10%.
[0013] Preferably, the lithium-rich layered positive electrode material is prepared by a molten salt method, a sol-gel method, or a coprecipitation method; and / or,
[0014] The particle size of the lithium-rich layered positive electrode material is between 100nm and 800nm.
[0015] Preferably, the lithium-rich layered cathode material comprises Li a Mn x Ni y Co z O2、Li a Mn x Ni y O2、Li a Mn x Ni y Co z Al w O2、Li a Mn x Ni y Al w At least one of O2, wherein x+y+z+w=1, 1<a<1.3.
[0016] Preferably, the stirring process lasts for 1 h to 4 h; and / or,
[0017] The dispersion is ultrasonic dispersion; preferably, the ultrasonic dispersion time is 30 min-60 min.
[0018] Preferably, the spray drying air volume is 200m 3 / h-400m 3 / h, the feed rate is 10ml / min-30ml / min, and the spray flow rate is 500L / h-700L / h.
[0019] Preferably, the heat treatment is performed in an air or oxygen atmosphere.
[0020] Preferably, the heating rate of the heat treatment process is 3°C / min-5°C / min, the heat treatment calcination temperature is 400°C-1000°C, and the heat treatment calcination time is 1h-4h.
[0021] In a second aspect, an embodiment of the present invention further provides a modified lithium-rich positive electrode material, wherein the modified lithium-rich positive electrode material is obtained by the processing method described in the first aspect.
[0022] In a third aspect, an embodiment of the present invention further provides a lithium-ion battery, comprising: a battery positive electrode made from the modified lithium-rich positive electrode material described in the second aspect above.
[0023] The modified lithium-rich positive electrode material prepared by the treatment method of the present invention has spheres formed by particle assembly through spray drying, which has higher porosity than the microspheres prepared by the traditional co-precipitation method, which is beneficial to improving the contact effect with the electrolyte and ensuring the capacity of the material.
[0024] The particles of the microspheres and the surface of the particles and the electrolyte are connected by silicates, which significantly improves the stability of the microsphere structure and the stability of the single particle interface, inhibits the irreversible escape of oxygen inside the material, and reduces side reactions at the interface.
[0025] High-temperature calcination is used to promote the diffusion of Si elements into the interior of the material, achieve gradient doping of Si elements near the surface of the material, and induce the production of spinel phase, which cooperates with the protective layer on the surface of the particles to further improve the stability of lattice oxygen, inhibit transition metal migration, and reduce capacity and voltage attenuation.
[0026] Batch modification is carried out directly through spray drying, which has a simple process, high preparation efficiency, high yield, and good electrochemical stability, and is conducive to industrial production and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A flow chart of a method for processing a lithium-rich layered positive electrode material provided in one embodiment of the present invention;
[0028] Figure 2 This is a scanning electron microscope image of the modified lithium-rich positive electrode material prepared in Example 1 of the present invention;
[0029] Figure 3 This is a projection electron microscope image of the modified lithium-rich positive electrode material prepared in Example 1 of the present invention;
[0030] Figure 4 This is a comparison chart of the cycle life of the modified lithium-rich positive electrode material prepared in Example 1 of the present invention and the lithium-rich layered positive electrode material prepared in Comparative Example 1 under 1C conditions;
[0031] Figure 5A comparison chart of the cycle life of the modified lithium-rich positive electrode material prepared in Example 2 of the present invention and the lithium-rich layered positive electrode material prepared in Comparative Example 1 under 0.5C conditions;
[0032] Figure 6 A comparison chart of the cycle life of the modified lithium-rich positive electrode material prepared in Example 3 of the present invention and the lithium-rich layered positive electrode material prepared in Comparative Example 1 under 1C conditions;
[0033] Figure 7 This is a scanning electron microscope image of the lithium-rich layered positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0035] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific processes and examples of materials, but those of ordinary skill in the art can be aware of the applicability of other processes and / or the use of other materials.
[0036] Please refer to Figure 1 In a first aspect, an embodiment of the present invention provides a method for processing a lithium-rich layered positive electrode material, the method comprising the following steps:
[0037] S10, mixing silicate with deionized water in a certain ratio to prepare a silicate solution;
[0038] S20, adding the lithium-rich layered positive electrode material to the silicate solution in a certain proportion, stirring and dispersing to form a suspension;
[0039] S30, spray drying the suspension to obtain a composite powder;
[0040] S40, heat-treating the composite powder to obtain a modified lithium-rich positive electrode material.
[0041] Specifically, the silicate includes at least one of lithium silicate, sodium silicate, and lithium sodium silicate.
[0042] Specifically, the concentration of the silicate solution is 0.5 g / L-5 g / L.
[0043] The mass ratio of the silicate to the lithium-rich layered positive electrode material is 1%-10%. Using the materials with the mass ratio for mixed spray drying is conducive to constructing a surface structure suitable for the capacity of the lithium-rich positive electrode material.
[0044] Specifically, the lithium-rich layered positive electrode material is prepared by one of a molten salt method, a sol-gel method, and a co-precipitation method.
[0045] The particle size of the lithium-rich layered positive electrode material is between 100nm and 800nm. Nano-scale lithium-rich layered positive electrode materials are conducive to spray drying to form a regular porous microsphere structure, while particles that are too large may result in the spraying result failing to achieve the particle aggregation effect.
[0046] Specifically, the lithium-rich layered positive electrode material includes Li a Mn x Ni y Co z O2、Li a Mn x Ni y O2、Li a Mn x Ni y Co z Al w O2、Li a Mn x Ni y Al w At least one of O2, wherein x+y+z+w=1, 1<a<1.3.
[0047] Specifically, the stirring process lasts for 1 h to 4 h.
[0048] Specifically, the dispersion is ultrasonic dispersion; preferably, the ultrasonic dispersion time is 30 min-60 min. Ultrasonication and stirring within the time range can make the nano single particles disperse better and fully contact and mix with the silicate solution, thereby improving the coating quality.
[0049] Specifically, the spray drying air intake volume is 200m 3 / h-400m 3 / h, the feed rate is 10ml / min-30ml / min, and the spray flow rate is 500L / h-700L / h. Spray drying under the spray conditions can obtain micron-assembled balls with uniform morphology, high tap density, and complete and uniform coating.
[0050] Specifically, the heat treatment is performed in air or oxygen atmosphere.
[0051] Specifically, the heating rate of the heat treatment process is 3°C / min-5°C / min, the heat treatment calcination temperature is 400°C-1000°C, and the heat treatment calcination time is 1h-4h. Heat treatment under the heat treatment conditions can make the Si surface of the material gradient doped and introduce a heterogeneous phase that is beneficial to structural stability.
[0052] In a second aspect, an embodiment of the present invention further provides a modified lithium-rich positive electrode material, wherein the modified lithium-rich positive electrode material is obtained by the processing method described in the first aspect.
[0053] In a third aspect, an embodiment of the present invention further provides a lithium-ion battery, comprising: a battery positive electrode made from the modified lithium-rich positive electrode material described in the second aspect above.
[0054] The specific process and effect of the treatment method of the lithium-rich layered positive electrode material of the present invention are further described in detail below in conjunction with some specific embodiments, but are not limited to the protection scope of the present invention.
[0055] Example 1
[0056] This embodiment prepares a modified lithium-rich positive electrode material, which specifically includes the following steps:
[0057] (1) Preparation of modified lithium-rich cathode materials:
[0058] Weigh 0.02g of Li2SiO3 to make a 0.5g / L solution, and then weigh 1g of nano-layered lithium-rich material Li prepared by the molten salt method with a particle size of about 200nm. 1.2 Mn 0.534 Ni 0.133 Co 0.133 O2. The lithium-rich material powder was dispersed in the Li2SiO3 solution, ultrasonicated for 30 minutes, stirred for 1 hour and then spray dried. The air volume during spraying was 400m 3 / h, the feed rate is 10ml / min, and the spray flow rate is 500L / h. The treated sample is placed in an alumina crucible and calcined to 600℃ and kept warm for 2h to obtain Li 1.2 Mn 0.534 Ni 0.133 Co 0.133 O2@2%Li2SiO3.
[0059] (2) Battery assembly:
[0060] Weigh 0.16 g of the modified lithium-rich positive electrode material prepared in step (1), add 0.02 g of super P (conductive carbon black) as a conductive agent and 0.02 g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply the mixture on an aluminum foil to make a positive electrode sheet, and assemble a CR2023 button cell in a vacuum glove box using a metal lithium sheet as a negative electrode, a polyethylene porous membrane as a separator, and 1 mol / L LiPF6 + 2 wt % LiBOB in EC:DMC:EMC (volume ratio 1:1:1) as an electrolyte.
[0061] Figure 2 This is an electron microscope scanning image of the modified lithium-rich positive electrode material prepared in Example 1. It can be seen from the image that the particles of the modified lithium-rich positive electrode material have high uniformity, the particles are tightly bound, and the structure is stable.
[0062] Figure 3 This is a perspective scan of the modified lithium-rich positive electrode material prepared in Example 1. It can be seen from the figure that the modified lithium-rich positive electrode material has Si elements evenly distributed, which is beneficial to improving the material performance.
[0063] Figure 4 This is a comparison chart of the cycle life of the buckle battery further prepared in Example 1 and the buckle battery prepared from ordinary lithium-rich layered positive electrode material in Comparative Example 1 under 1C conditions. It can be seen from the figure that the cycle attenuation corresponding to the modified lithium-rich positive electrode material is significantly smaller than the cycle attenuation corresponding to the ordinary lithium-rich layered positive electrode material.
[0064] Example 2
[0065] This embodiment prepares a lithium-rich layered positive electrode material, which specifically includes the following steps:
[0066] (1) Preparation of modified lithium-rich cathode materials:
[0067] Weigh 0.01g of Na2SiO3 to make a 0.5g / L solution, and then weigh 1g of nano-layered lithium-rich material Li prepared by the sol-gel method with a particle size of about 200nm. 1.2 Mn 0.534 Ni 0.133 Co 0.133 O2. The lithium-rich material powder was dispersed in the Na2SiO3 solution, ultrasonicated for 30 minutes, stirred for 1 hour and then spray dried. The air volume during spraying was 400m 3 / h, the feed rate is 10ml / min, and the spray flow rate is 500L / h. The treated sample is placed in an alumina crucible and calcined to 600℃ and kept warm for 2h to obtain Li 1.2 Mn 0.534 Ni 0.133 Co 0.133 O2@1%Na2SiO3.
[0068] (2) Battery assembly:
[0069] Weigh 0.16 g of the modified lithium-rich positive electrode material prepared in step (1), add 0.02 g of super P (conductive carbon black) as a conductive agent and 0.02 g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply the mixture on aluminum foil to make a positive electrode sheet, and assemble a CR2023 button cell in a vacuum glove box using a metal lithium sheet as a negative electrode, a polyethylene porous membrane as a separator, and 1 mol / L LiPF6 + 2% LiBOB in EC:DMC:EMC (volume ratio 1:1:1) as an electrolyte.
[0070] Figure 5 This is a comparison chart of the cycle life of the buckle battery further prepared in Example 2 and the buckle battery prepared from the ordinary lithium-rich layered positive electrode material in Comparative Example 1 under 0.5C conditions. It can be seen from the figure that the cycle attenuation corresponding to the modified lithium-rich positive electrode material is significantly smaller than the cycle attenuation corresponding to the ordinary lithium-rich layered positive electrode material.
[0071] Example 3
[0072] This embodiment prepares a modified lithium-rich layered positive electrode material, which specifically includes the following steps:
[0073] (1) Preparation of modified lithium-rich cathode materials:
[0074] Weigh 0.02g of Li2SiO3 to make a 0.5g / L solution, and then weigh 1g of nano-layered lithium-rich material Li prepared by co-precipitation method with a particle size of about 400nm. 1.15 Mn 0.56 Ni 0.2 Al 0.04 O2. The lithium-rich material powder was dispersed in the Li2SiO3 solution, ultrasonicated for 30 minutes, stirred for 1 hour and then spray dried. The air volume during spraying was 400m 3 / h, the feed rate is 10ml / min, and the spray flow rate is 500L / h. The treated sample is placed in an alumina crucible and calcined to 600℃ and kept warm for 2h to obtain Li 1.1 5Mn 0.56 Ni 0.2 Al 0.04 O2@2%Li2SiO3.
[0075] (2) Battery assembly:
[0076] Weigh 0.16 g of the modified lithium-rich positive electrode material prepared in step (1), add 0.02 g of super P (conductive carbon black) as a conductive agent and 0.02 g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply the mixture on aluminum foil to make a positive electrode sheet, and assemble a CR2023 button cell in a vacuum glove box using a metal lithium sheet as a negative electrode, a polyethylene porous membrane as a separator, and 1 mol / L LiPF6 + 2% LiBOB in EC:DMC:EMC (volume ratio 1:1:1) as an electrolyte.
[0077] Figure 6 This is a comparison chart of the cycle life of the buckle battery further prepared in Example 3 and the buckle battery prepared from the ordinary lithium-rich layered positive electrode material in Comparative Example 1 under 1C conditions. It can be seen from the figure that the cycle attenuation corresponding to the modified lithium-rich positive electrode material is significantly smaller than the cycle attenuation corresponding to the ordinary lithium-rich layered positive electrode material.
[0078] Comparative Example 1
[0079] Battery assembly:
[0080] Weigh 0.16g of nano lithium-rich layered positive electrode material prepared by the molten salt method, add 0.02g of super P (conductive carbon black) as a conductive agent and 0.02g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply the mixture on aluminum foil to make a positive electrode sheet, and in a vacuum glove box, use a metal lithium sheet as a negative electrode, a polyethylene porous membrane as a separator, and 1mol / LLiPF6+2%LiBOB in EC:DMC:EMC (volume ratio 1:1:1) as an electrolyte to assemble a CR2023 button battery.
[0081] Figure 5 This is an electron microscope scanning image of the nano lithium-rich layered positive electrode material used in Comparative Example 1. It can be seen from the image that the conventional nano lithium-rich layered positive electrode material particles have low uniformity, the particles are not tightly bound, and there are gaps.
[0082] The cycle life comparison of the buckle battery prepared in comparative example 1 under 1C condition is shown in the figure Figure 4 As shown, its cycle attenuation is significantly lower than that of the buckle prepared by the modified lithium-rich positive electrode material in Example 1.
[0083] The modified lithium-rich positive electrode material prepared by the treatment method of the present invention has spheres formed by particle assembly through spray drying, which has higher porosity than the microspheres prepared by the traditional co-precipitation method, which is beneficial to improving the contact effect with the electrolyte and ensuring the capacity of the material.
[0084] The particles of the microspheres and the surface of the particles and the electrolyte are connected by silicates, which significantly improves the stability of the microsphere structure and the stability of the single particle interface, inhibits the irreversible escape of oxygen inside the material, and reduces side reactions at the interface.
[0085] High-temperature calcination is used to promote the diffusion of Si elements into the interior of the material, achieve gradient doping of Si elements near the surface of the material, and induce the production of spinel phase, which cooperates with the protective layer on the surface of the particles to further improve the stability of lattice oxygen, inhibit transition metal migration, and reduce capacity and voltage attenuation.
[0086] Batch modification is carried out directly through spray drying, which has a simple process, high preparation efficiency, high yield, and good electrochemical stability, and is conducive to industrial production and commercial application.
[0087] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0088] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for processing a lithium-rich layered positive electrode material, characterized in that: The processing method comprises the following steps: S10, mixing silicate with deionized water in a certain ratio to prepare a silicate solution; S20, adding the lithium-rich layered positive electrode material to the silicate solution in a certain proportion, stirring and dispersing to form a suspension; S30, spray drying the suspension to obtain a composite powder; S40, heat-treating the composite powder to obtain a modified lithium-rich positive electrode material.
2. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The silicate comprises at least one of lithium silicate, sodium silicate and lithium sodium silicate; and / or, The concentration of the silicate solution is 0.5 g / L-5 g / L; and / or, The mass ratio of the silicate to the lithium-rich layered positive electrode material is 1%-10%.
3. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The lithium-rich layered positive electrode material is prepared by a molten salt method, a sol-gel method, or a coprecipitation method; and / or, The particle size of the lithium-rich layered positive electrode material is between 100nm and 800nm.
4. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The lithium-rich layered positive electrode material includes Li a Mn x Ni y Co z O2、Li a Mn x Ni y O2、Li a Mn x Ni y Co z Al w O2、Li a Mn x Ni y Al w At least one of O2, wherein x+y+z+w=1, 1<a<1.
3.
5. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The stirring process lasts for 1 hour to 4 hours; and / or, The dispersion is ultrasonic dispersion; preferably, the ultrasonic dispersion time is 30 min-60 min.
6. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The spray drying air volume is 200m 3 / h-400m 3 / h, the feed rate is 10ml / min-30ml / min, and the spray flow rate is 500L / h-700L / h.
7. The method for processing lithium-rich layered positive electrode materials according to claim 1, characterized in that: The heat treatment is performed in air or oxygen atmosphere.
8. The method for processing lithium-rich layered cathode materials according to claim 1, characterized in that: The heating rate of the heat treatment process is 3°C / min-5°C / min, the heat treatment calcination temperature is 400°C-1000°C, and the heat treatment calcination time is 1h-4h.
9. A modified lithium-rich cathode material, characterized in that: The lithium-rich layered positive electrode material is obtained by the processing method described in any one of claims 1-8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises: a battery positive electrode made from the modified lithium-rich positive electrode material according to claim 9.
Citation Information
Patent Citations
Preparation method of lithium-rich anode material
CN103094550A
Lithium manganate composite positive electrode material, a preparing method thereof and a lithium-ion battery
CN104347853A
Silicon-containing lithium-rich manganese-based layered lithium-ion battery positive electrode material and preparation method thereof
CN105185955A
High-capacity solid lithium ion battery and preparation method thereof
CN107706393A
Composite positive electrode lithium supplementing material and preparation method and application thereof
CN116759577A